Sexual health, alcohol and the university environment: Is there a need for sexual health promotion intervention? - Burns, Sharyn (2015)
© CSIRO 2015. Background: Young university students participate in hazardous drinking and risky sexual health behaviours, however there are few comprehensive interventions targeting this group. Methods: Undergraduate university students aged 18-24 years (n=2466) were recruited to complete an online survey to investigate the association between levels of alcohol consumption, gender and experienced, second-hand and witnessed sexual health behaviours and situations. Results: Male students and hazardous drinkers were most likely to participate in unprotected sex and regretted sex. Female students and hazardous drinkers were most likely to experience an unwanted sexual advance. Conclusions: Integrated and comprehensive interventions targeting young people in the university setting are needed.